Validation of the professional competencies model required by experts of agricultural consulting, technical, and engineering services companies to provide private extension services - Farshad, Sanaz; Niknami, Mehrdad (Frontiers in Sustainable Food Systems, 2024)
One of the important pillars for achieving organizational objectives is the presence of qualified human resources. Professional competencies in experts working in agricultural consulting, technical, and engineering services companies (ACTESCs) can be a basis for the quality of human resources and assure the quality of the functions of this system. Accordingly, this study aimed to identify the professional competencies required by extension experts working in these companies to provide extension services from their perspectives. The research method was a survey. The statistical population of the study consisted of 593 extension experts working in these companies, from whom 234 people were selected as the sample by the use of Cochran's formula. In the field stage, a questionnaire was used as the main research tool. The face and content validities as well as the reliability of the research tool were confirmed. The result of the structural equation modeling approach confirmed the hypothesis that economic, technical, and communicational functions play roles in providing extension services. Accordingly, it is recommended to fill the gap between the existing competencies and the competencies required by the experts working in the ACTESCs to provide appropriate Private Extension Services (PESs).